Rubber Plantation Management for Increased Productivity - Kaewnoy, Yongyuth; Pakittawichit, Thananchakorn; Sukhaparamate, Supawat (Interdisciplinary Academic and Research Journal, 2024)
Background and Objectives: This article presents effective strategies and methods to increase rubber production in rubber plantations through the utilization of modern technologies and process improvements. It begins with site preparation and the selection of suitable rubber tree varieties, followed by proper tree maintenance and timely rubber tapping. Additionally, the article introduces innovative technologies capable of enhancing rubber yield and quality efficiently. These approaches aim to establish sustainable rubber plantation management practices that have a positive impact on rubber production in both the current and future rubber industry. Methodology: This study is a study of related documents and research. Analyze and present according to the educational objectives. Results: Managing rubber plantations to increase production must rely on knowledge gained from continuous study and research. This knowledge includes selecting rubber species that are appropriate to the soil and weather conditions in each area. Using modern methods of planting and tapping rubber. Soil maintenance and proper use of fertilizers. Conclusions: Choosing the right species, nourishing the soil, and using fertilizers appropriately. Pest and disease control and tapping rubber in a way that makes the rubber tree last a long time Including government support in education, research, and access to technology are things that can manage rubber plantations.